Approaches for attaining clean bacterial fractions from complex environmental samples - Yu, Jaeyoung; Kawahisa, Marika; Kinoshita, Aya; Zulmajdi, Abdullah Adham; Mori, Tetsushi (Frontiers in Marine Science, 2024)
Marine bacteria have been targeted by industry and pharmaceutics as genetic resources for highly active enzymes or novel lead compounds. Although numerous techniques have been introduced to isolate useful bacteria from the environment, we are still highly dependent on the conventional direct cultivation method to attain pure cultures. However, efficient bacterial isolation is hindered by several factors, including the presence of impurities. In this work, to demonstrate the significance of removing impurities and their impact on bacterial isolation, we employed two approaches: dielectrophoresis (DEP) and fluorescent D-amino acids (FDAA). We successfully attained clean bacterial fractions applicable for downstream processing using these approaches, uniquely designed to identify bacteria based on their characteristics and features. The diversity of bacteria attained by both approaches was investigated using 16S rRNA sequencing and compared to that attained by the standard differential centrifugation method. In addition, the viability of the isolates was also determined via direct cultivation. As a result, the separation of bacteria from impurities allowed for the identification of novel and useful bacteria unique to each approach. Successful cultivation also suggested that both approaches were applicable for attaining viable bacteria. In conclusion, removing impurities to attain clean bacterial fractions promotes the isolation of novel bacteria and thus could aid in the successful isolation of useful bacteria within complex environmental samples.